Leiomyoma of the esophagus: A case report and review of the literature. (May 2022) - Beji, Hazem; Bouassida, Mahdi; Kallel, Yassine; Tormane, Mohamed Amine; Mighri, Mohamed Mongi; Touinsi, Hassen
Abstract: Introduction: Benign tumors represent less than 1% of esophageal neoplasms. Esophageal leiomyoma is a very rare tumor that arises from mesenchymal tissue. We present here a case of leiomyoma of the esophagus which was revealed by dysphagia and vomiting that was treated by surgical enucleation. Presentation of case: This report illustrates the case of a female who presented with dysphagia and vomiting. Imageology demonstrated an esophageal mass which was treated with surgical enucleation. Histopathology confirmed the diagnosis of leiomyoma. Clinical discussion: Benign esophageal tumors are rare. Leiomyoma commonly presents as a single lesion in the middle or lower third of the esophagus. Leiomyomas located in the proximal and middle third of the esophagus can be operated on by right thoracotomy. Surgical treatment varies from enucleation to esophageal resection depending on the size and location of the mass. In our case, the tumor was enucleated by a right posterolateral thoracotomy. Conclusion: Esophageal leiomyoma is a benign and generally asymptomatic tumor. Surgery is the pillar of treatment. Enucleation should be performed whenever possible to avoid esophagectomy and thus decrease morbidity and mortality. Highlights: Esophageal leiomyoma is a very rare tumor that arises from mesenchymal tissue. An enhanced computed tomography scan with oral contrast or endoscopic ultrasonography is essential to assess the diagnosis. Surgery consists of enucleation or esophagectomy depending on the location and size of the tumor.